Information and communication technology among MSMEs: Drivers and Barriers - Yuwono, Tri; Novandari, Weni; Suroso, Agus; Sudarto, Sudarto (Eastasouth Institute, 2024)
There is an increasing trend of Information and Communication Technology (ICT) among micro, small, and medium enterprises (MSMEs) today. However, implementing ICT in MSMEs is still challenging due to financial and resource limitations. This study identifies and analyzes the driving and inhibiting factors affecting ICT implementation in MSMEs. Data from 175 MSMEs were analyzed using quantitative descriptive techniques in percentages and smart PLS for confirmatory factor analysis (CFA). Based on the analysis results, nine driving factors and eleven inhibiting factors for ICT adoption in MSMEs were found. Although much research has been conducted in the field of ICT, there is still a need to adjust strategies and policies that can support ICT adoption for MSMEs, especially in developing countries.